2020
DOI: 10.1002/jmv.26245
|View full text |Cite
|
Sign up to set email alerts
|

Intratonsillar detection of 27 distinct viruses: A cross‐sectional study

Abstract: Palatine tonsils have been observed to harbor several distinct respiratory and herpesviruses in separate studies. In this study, the presence of these viruses in palatine tonsils was comprehensively studied in both children and adults. A cross‐sectional analysis of 181 patients (median age 22 years; range, 2.6‐66) operated for a benign tonsillar disease was conducted. Real‐time polymerase chain reaction was performed to detect 27 distinct viruses in all: eight human herpesviruses, 16 respiratory viruses, parvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
4
16
0
1
Order By: Relevance
“…HBoV1 DNA was detected by PCR in tonsil and/or NPA samples in 17% of the study patients; the prevalence in the tonsil tissue samples was 8%. This is in line with earlier studies 9,12 . Furthermore, HBoV infections are most prevalent in small children, showing prolonged virus shedding in the nasopharynx after acute infection, whereas they become less common with age 24 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…HBoV1 DNA was detected by PCR in tonsil and/or NPA samples in 17% of the study patients; the prevalence in the tonsil tissue samples was 8%. This is in line with earlier studies 9,12 . Furthermore, HBoV infections are most prevalent in small children, showing prolonged virus shedding in the nasopharynx after acute infection, whereas they become less common with age 24 .…”
Section: Discussionsupporting
confidence: 91%
“…In‐house real‐time PCRs were used as described for HBoV1, enterovirus, rhinovirus, and respiratory syncytial virus 20–22 . Primer sequences of HBoV1 have been previously described 9 . Seeplex RV12 ACE Detection (Seegene, Seoul, Korea) multiplex PCR assay was applied for adenovirus, coronaviruses (229 E/NL63 and OC43/HKU1), influenza A and B viruses, metapneumovirus, parainfluenza virus types 1–3, respiratory syncytial virus groups A and B, and rhinovirus, according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clustering of integrin receptors causes aggregation of the caveolae, resulting in large invaginations of the plasma membrane, which are then colonized by streptococci [20]. Some streptococci, using M-protein-bound fibronectin, induce focal adhesion complexes and penetrate the cell membrane by one of two mechanisms -zipper-like mechanism or membrane ruffling [21]. The first mechanism directs streptococci to a safer cavernous-somatic compartment of the cell, and the second directs bacteria to phagolysosomes, where most of them are destroyed.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…But, it should be added that there was no difference in virus detection between groups at the intratonsillar level in the same study [ 18 ]. In a recent cross-sectional study in which pediatric and adult patients undergoing tonsillectomy were included (mean age 22), it was shown that no virus was shown to be associated with tonsil diseases and respiratory diseases [ 19 ]. The wide age range of the study may be associated with this result.…”
mentioning
confidence: 99%